2009
DOI: 10.1002/app.30075
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐interpenetrating networks based on poly(N‐isopropyl acrylamide) and poly(N‐vinylpyrrolidone)

Abstract: Three series of novel semi-interpenetrating polymer networks, based on crosslinked poly(N-isopropylacrylamide), PNIPA, and different amounts of the linear poly(N-vinylpyrrolidone), PVP, were synthesized to improve the mechanical properties and thermal response of PNIPA gels. The effect of the incorporation of the linear PVP into the temperature responsive networks on the temperature-induced transition, swelling/deswelling behavior, and mechanical properties was studied. Polymer networks with four different cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous IPN studies have reported similar deviations in failure properties within sample groups. 16,55 Failure point determination in unconfined compressive testing can be difficult because a partially fractured gel still supports a compressive load, and therefore tensile mechanical data are usually preferred for analysis of failure properties. In spite of these drawbacks, compressive testing with characterization of failure strain is necessary for evaluation of potential materials for cartilage implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous IPN studies have reported similar deviations in failure properties within sample groups. 16,55 Failure point determination in unconfined compressive testing can be difficult because a partially fractured gel still supports a compressive load, and therefore tensile mechanical data are usually preferred for analysis of failure properties. In spite of these drawbacks, compressive testing with characterization of failure strain is necessary for evaluation of potential materials for cartilage implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogels were prepared by crosslinking polymerization (24 h at 4°C) of NIPA monomers (molar fraction m mon = 0.885 mol L -1 ) by using N,N 0 -methylenebisacrylamide (BIS) (m cr = 35.4 mmol L -1 ) as a crosslinker. 55 Equilibrium swelling diagrams on gels with the lowest (ψ = 0) and highest (ψ = 3 wt%) mass fractions of PVP chains are depicted in Figs 4(A) and 4(B) together with results of numerical simulation, and those on gels with intermediate ψ values (ψ = 1 and 2 wt%) are presented in Figs S1A and S1B.…”
Section: Copolymer Gelsmentioning
confidence: 99%
“…We now approximate observations on double‐network semi‐interpenetrating PNIPA gels prepared in aqueous solutions of poly( N ‐vinylpyrrolidone) (PVP) (molecular weight M w = 1.3 × 10 6 g mol –1 ) with various mass fractions ψ of PVP chains ranging from 0 to 3 wt%. The hydrogels were prepared by crosslinking polymerization (24 h at 4 °C) of NIPA monomers (molar fraction m mon = 0.885 mol L –1 ) by using N , N ′‐methylenebisacrylamide (BIS) ( m cr = 35.4 mmol L –1 ) as a crosslinker 55 . Equilibrium swelling diagrams on gels with the lowest ( ψ = 0) and highest ( ψ = 3 wt%) mass fractions of PVP chains are depicted in Figs 4(A) and 4(B) together with results of numerical simulation, and those on gels with intermediate ψ values ( ψ = 1 and 2 wt%) are presented in Figs S1A and S1B.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(77) are influenced by the concentration of monomers C mon , we approximate the swelling diagrams [42] for PNIPA gels with C mon = 100. [19].…”
Section: Unconstrained Swellingmentioning
confidence: 99%